Bioenergetic biomarkers as predictive indicators and their relationship with cognitive function in newly diagnosed, drug-naïve patients with bipolar disorder - Ting Cao; BaoYan Xu; SuJuan Li; Yan Qiu; JinDong Chen; HaiShan Wu; HuaLin Cai (Translational Psychiatry)
Abstract Mitochondrial dysfunction and disrupted bioenergetic processes are critical in the pathogenesis of bipolar disorder (BD), with cognitive impairment being a prominent symptom linked to mitochondrial anomalies. The tricarboxylic acid (TCA) cycle, integral to mitochondrial energy production, may be implicated in this cognitive dysfunction, yet its specific association with BD remains underexplored. In this cross-sectional study, 144 first-episode, drug-naive BD patients and 51 healthy controls were assessed. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS), serum TCA cycle metabolites were quantified, and cognitive function was evaluated through the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and the Stroop color-word test. The study found that BD patients exhibited significantly elevated serum levels of several TCA metabolites compared to healthy controls, alongside lower cognitive function scores. Correlational analyses revealed that certain bioenergetic metabolites were significantly positively associated with anxiety and negatively correlated with cognitive performance in BD patients. Notably, succinic acid, α-Ketoglutaric acid (α-KG), and malic acid emerged as independent risk factors for BD, with their combined profile demonstrating diagnostic utility. These findings underscore the potential of serum bioenergetic metabolites as biomarkers for BD, providing insights into the mitochondrial dysfunction underlying cognitive impairment and offering a basis for early diagnosis and targeted therapeutic strategies.